Celebrating 50 years of ACAL Selected papers from the 50th Annual Conference on African Linguistics (Volume 7) - Akinlabi, Akinbiyi; Bickmore, Lee; Cahill, Michael; Diercks, Michael; Downing, Laura J.; Essegbey, James; Franich, Katie; McPherson, Laura; Rose, Sharon (Language Science Press, 2021)
The papers in this volume were presented at the 50th Annual Conference on African Linguistics held at the University of British Columbia in 2019. The contributions span a range of theoretical topics as well as topics in descriptive and applied linguistics. The papers reflect the typological and genetic diversity of languages in Africa and also represent the breadth of the ACAL community, with papers from both students and more senior scholars, based in North America and beyond. They thus provide a snapshot on current research in African linguistics, from multiple perspectives. To mark the 50th anniversary of the conference, the volume editors reminisce, in the introductory chapter, about their memorable ACALs.